Discrimination of the prochiral hydrogens at the C-2 position of n-alkanes by the methane/ammonia monooxygenase family proteins1. Issue 30 (14th August 2015) - Miyaji, Akimitsu; Miyoshi, Teppei; Motokura, Ken; Baba, Toshihide
<x xml:space="preserve">Abstract</x> The substrate binding site of AMO/pMMO family proteins can discriminate between the prochiral hydrogens at the C-2 position of n-alkanes. We predict that at least one of the three amino acid residues at the di-copper site affects the discriminating ability of the family proteins.